Bacillus subtilis and Rhizophagus intraradices improve vegetative growth, yield, and fruit quality of Fragaria × ananassa var. San Andreas - Huasasquiche Sarmiento, Lucero (2024)
Strawberry cultivation requires strategies that maintain or improve its yield within a scheme in which reducing fertilizers and other chemical products can make its consumption safer and more environmentally friendly. This study aims to evaluate the effect of Bacillus subtilis and Rhizophagus intraradices on strawberry growth, yield, and fruit quality. B. subtilis and R. intraradices were inoculated and co-inoculated under three fertilization levels of 225-100-250, 112-50-125, and 0-0-0 kg・ha−1 of N, P2O5 and K2O. Vegetative growth was evaluated in plant height (cm), leaf area (cm2), aerial fresh weight (g), aerial dry weight (g), and plant coverage (%) variables. Fruit quality parameters such as total acidity (g・100 mL−1), soluble solids (Brix◦), and firmness (kg) were also determined, as well as the number of fruits per m2 and yield (t・ha−1). The results showed that the pre-treatment of root immersion in a nutrient solution with B. subtilis and the fractionation of 6 L B. subtilis inoculation per plant at a concentration of 107 CFU・mL−1, in combination with 225-100-250 kg・ha−1 of N, P2O5, and K2O, achieved the highest accumulation of dry matter (12.9 +- 1.9 g・plant−1), the highest number of fruits (28.2 +- 4.5 fruits・m−2), and the highest yield (7.2 +- 1.4 t・ha−1). In addition, this treatment increased the soluble sugar content by 34.78% and fruit firmness by 26.54% compared to the control without inoculation. This study highlights the synergistic effect of mineral nutrition and microbial inoculation with B. subtilis in increasing strawberry yield and fruit quality.